Analisa Suhu Pembakaran Sampah Kering Sebagai Potensi Energi Panas Untuk Proses Pengeringan - Angga Darma Prabowo; Hadi Prayitno; Dondi Kurniawan; Martinus; Ahmad Yonanda (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2026)
Waste management poses a significant environmental challenge, yet dry waste holds potential as a renewable energy source through Waste-to-Energy (WTE) technology. This study aims to analyze the potential of utilizing heat from dry waste combustion for drying applications using a hybrid approach of experimental methods and Computational Fluid Dynamics (CFD) simulation. The experimental stage was conducted by burning dry waste in a furnace to obtain the average hot gas temperature, which was measured at 295.33°C. This value was then used as a boundary condition in the CFD simulation of an integrated heat exchanger system within the furnace. Air at a temperature of 30°C was flowed into the heat exchanger with four mass flow rate variations (0.087, 0.092, 0.126, and 0.165 kg/s). The simulation results show that the system is capable of heating the air to a temperature range of 46.05°C to 58.05°C, which is ideal for drying applications. An inverse relationship was found between the mass flow rate and the outlet temperature, where a lower flow rate results in hotter air. This research proves that the heat recovery system from dry waste combustion is technically feasible and has the potential to be a sustainable alternative energy solution for drying processes.